Secant of an elipse for a parameter

Geometry Level 3

A line p p is a secant of an elipse e e for all k k 's from which of the following sets?

p : 2 x + 3 y 2 k = 0 p:2x + 3y - 2k = 0 , e : 2 x 2 8 x + y 2 + 2 y = 0 e:2{x^2} - 8x + {y^2} + 2y = 0

( 1 11 2 ; 1 + 11 2 ) \left( {\frac{{1 - \sqrt {11} }}{2};\frac{{1 + \sqrt {11} }}{2}} \right) ( 1 4 11 2 ; 1 + 4 11 2 ) \left( {\frac{{1 - 4\sqrt {11} }}{2};\frac{{1 + 4\sqrt {11} }}{2}} \right) This never happens. ( 1 3 11 2 ; 1 + 3 11 2 ) \left( {\frac{{1 - 3\sqrt {11} }}{2};\frac{{1 + 3\sqrt {11} }}{2}} \right) ( 1 8 11 2 ; 1 + 8 11 2 ) \left( {\frac{{1 - 8\sqrt {11} }}{2};\frac{{1 + 8\sqrt {11} }}{2}} \right)

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tomáš Hauser
Jun 12, 2019

For p to be the secant of e, there must be two intersecting points which means that there must be two solutions to the equation and this happnes only if discriminant is greater than zero:
p : 2 x + 3 y 2 k = 0 y = 2 k 2 x 3 e : 2 x 2 8 x + y 2 + 2 y = 0 2 x 2 8 x + ( 2 k 2 x 3 ) 2 + 2 ( 2 k 2 x 3 ) = 0 2 x 2 8 x + 4 k 2 8 k x + 4 x 2 9 + 4 k 4 x 3 = 0 18 x 2 72 x + 4 k 2 8 k x + 4 x 2 + 12 k 12 x = 0 22 x 2 84 x 8 k x + 4 k 2 + 12 k = 0 22 x 2 x ( 84 + 8 k ) + ( 4 k 2 + 12 k ) = 0 D = ( 84 + 8 k ) 2 4 22 ( 4 k 2 + 12 k ) D = 7056 + 1344 k + 64 k 2 352 k 2 1056 k D = 288 k 2 + 288 k + 7056 D > 0 288 k 2 + 288 k + 7056 > 0 18 k 2 18 k 441 < 0 k 1 , 2 = 18 ± 18 2 4 18 ( 441 ) 36 = 18 ± 32076 36 = 18 ± 54 11 36 = 1 ± 3 11 2 k ( 1 3 11 2 ; 1 + 3 11 2 ) \begin{array}{l} p:2x + 3y - 2k = 0 \Rightarrow y = \frac{{2k - 2x}}{3}\\ e:2{x^2} - 8x + {y^2} + 2y = 0\\ 2{x^2} - 8x + {\left( {\frac{{2k - 2x}}{3}} \right)^2} + 2 \cdot \left( {\frac{{2k - 2x}}{3}} \right) = 0\\ 2{x^2} - 8x + \frac{{4{k^2} - 8kx + 4{x^2}}}{9} + \frac{{4k - 4x}}{3} = 0\\ 18{x^2} - 72x + 4{k^2} - 8kx + 4{x^2} + 12k - 12x = 0\\ 22{x^2} - 84x - 8kx + 4{k^2} + 12k = 0\\ 22{x^2} - x \cdot \left( {84 + 8k} \right) + \left( {4{k^2} + 12k} \right) = 0\\ D = {\left( {84 + 8k} \right)^2} - 4 \cdot 22 \cdot \left( {4{k^2} + 12k} \right)\\ D = 7056 + 1344k + 64{k^2} - 352{k^2} - 1056k\\ D = - 288{k^2} + 288k + 7056\\ D{\rm{ > }}0\\ - 288{k^2} + 288k + 7056{\rm{ > }}0\\ 18{k^2} - 18k - 441 < 0\\ {k_{1,2}} = \frac{{18 \pm \sqrt {{{18}^2} - 4 \cdot 18 \cdot \left( { - 441} \right)} }}{{36}} = \frac{{18 \pm \sqrt {32076} }}{{36}} = \frac{{18 \pm 54\sqrt {11} }}{{36}} = \frac{{1 \pm 3\sqrt {11} }}{2}\\ k \in \left( {\frac{{1 - 3\sqrt {11} }}{2};\frac{{1 + 3\sqrt {11} }}{2}} \right) \end{array}

Is the title of this problem correct? ("Arithmetic series problem")

Chris Lewis - 1 year, 11 months ago

No, thanks. I guess I wanted to make a different problem at first, so that may be why. :D

Tomáš Hauser - 1 year, 11 months ago

Log in to reply

Ah, this title makes more sense!!

Chris Lewis - 1 year, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...